Analisis Pemahaman Konsep Radiasi Benda Hitam Berbantuan PhET Simulation untuk Menentukan Konstanta Wien - Hertika, Indri; Patricia, Amanda; Siregar, Dinaulina; Simanungkalit, Ferawati; Harahap, Nadia Ulfah (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to improve the understanding of the concept of physics education study program students, quantum physics courses on black-body radiation material to determine the wien constant. With the help of PhET simulation through descriptive approach with software-based experimental method. The results showed that the use of PhET simulations was very good at improving students' understanding of concepts, the percentage of practicality and feasibility was 92.8%, respectively.